2020
DOI: 10.1021/acs.inorgchem.0c01641
|View full text |Cite
|
Sign up to set email alerts
|

Simpler and Cleaner Synthesis of Variously Capped Cobalt Nanocrystals Applied in the Semihydrogenation of Alkynes

Abstract: Unlike the classical organometallic approach, we report here a synthetic pathway requiring no reducing sources or heating to produce homogenous hexagonal close packed cobalt nanocrystals (NCs). Involving a disproportionation process, this simple and fast (6 min) synthesis is performed at room temperature in presence of eco-friendly fatty alcohols to passivate Co NCs. Through a recycling step, the yield of Co NCs is improved and the waste generation is limited making this synthetic route cleaner. After an easy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…In order to further confirm the bind between OA molecules and Co-NiS, fresh Fe 3 O 4 and MnO 2 nanoparticles were modified with OA (see Methods section for details) and the corresponding Fourier transform infrared (FTIR) spectra are shown in Figure D. The double absorption peaks between 3400 and 3500 cm –1 emerge in the FTIR spectra of both OA-modified Fe 3 O 4 and MnO 2 , which could be attributed to symmetrical and asymmetrical stretching vibration of -NH 2 , verifying the bind between OA molecules and Co-NiS. Subsequently, the colloidal Co-NiS nanorod cyclohexane dispersion was added into the aqueous MXene colloidal dispersion.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In order to further confirm the bind between OA molecules and Co-NiS, fresh Fe 3 O 4 and MnO 2 nanoparticles were modified with OA (see Methods section for details) and the corresponding Fourier transform infrared (FTIR) spectra are shown in Figure D. The double absorption peaks between 3400 and 3500 cm –1 emerge in the FTIR spectra of both OA-modified Fe 3 O 4 and MnO 2 , which could be attributed to symmetrical and asymmetrical stretching vibration of -NH 2 , verifying the bind between OA molecules and Co-NiS. Subsequently, the colloidal Co-NiS nanorod cyclohexane dispersion was added into the aqueous MXene colloidal dispersion.…”
Section: Results and Discussionmentioning
confidence: 99%
“…48 Previously we showed that our unsupported Co NPs were able to catalyze the reduction of alkyne to alkene in presence of hydrogen. 49 Thus, we designed a specific setup in an H-tube, formed by a glass link between two microwaves vials, and spherical Co NPs in OAm at 190°C were introduced on one side and spherical Co NPs with diphenylacetylene (DPA) were mixed in toluene on the other side at RT (Scheme 2).…”
Section: Article |mentioning
confidence: 99%
“…It was established that similar spherical cobalt NPs can be obtained with bromine and iodine complex derivatives using the same redox pathway. 25,49 In literature, it is also mentioned that bromine 55,56 and on rare occasions iodine 57 were able to induce oxidative etching allowing the production of Co NRs through a similar mechanism. [CoBr(PPh3)3] and [CoI(PPh3)3] were synthesized and Co NRs were obtained after 10h and 18h, respectively (Fig.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…A recent study by the group of Petit [72] used the commercial Co(I) precursor [CoCl(PPh 3 ) 3 ] to generate cobalt nanoparticles via disproportionation in THF. Rapid agglomeration and subsequent deactivation of the catalyst was inhibited by the addition of fatty alcohols.…”
Section: Cobalt[ 11 27 ...mentioning
confidence: 99%
“… The hypothesized catalytic cycles involved in the photochemical transfer semi‐hydrogenation of alkynes. [72] …”
Section: Cobalt[ 11 27 ...mentioning
confidence: 99%